2015
DOI: 10.21608/jppp.2015.53664
|View full text |Cite
|
Sign up to set email alerts
|

Bioloical Aspects and Life Table Parameters of the Cotton Leaf–worm, Spodoptera Littoralis (Boisd.), on Different Vegetable Host Plants.

Abstract: The various aspects of the biology of the cotton leaf-worm ,Spodoptera littoralis (Boisd.) ((Lepidoptera: Noctuidae)where it fed on four different vegetable plants okra , squash,cabbage and green beans to study the effect of these host plants on the developmental stages, fecundity and life table parameters under laboratory conditions of (25±1°C) and 75±5%R.H.Obtanied results and statistical analysis cleared that the developmental stages, fecundity and life table parameters affected by different hosts whereas t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
2
0
0
Order By: Relevance
“…In addition, the data obtained in the current work suggest low fertility of eggs laid by S. littoralis larvae fed on melon plants. The fecundity and fertility of S. littoralis females may be influenced by the host plant; in fact, cucurbitaceans are preferred plants for S. littoralis feeding but negatively affect insect reproductive parameters [38,39]. Our results were consistent with previous studies on lepidopteran pests showing a reduction in the lifespan and reproductive potential of insects fed on EPF-colonized plants or their offspring [25,31,36].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, the data obtained in the current work suggest low fertility of eggs laid by S. littoralis larvae fed on melon plants. The fecundity and fertility of S. littoralis females may be influenced by the host plant; in fact, cucurbitaceans are preferred plants for S. littoralis feeding but negatively affect insect reproductive parameters [38,39]. Our results were consistent with previous studies on lepidopteran pests showing a reduction in the lifespan and reproductive potential of insects fed on EPF-colonized plants or their offspring [25,31,36].…”
Section: Discussionsupporting
confidence: 90%
“…Differences in the plant volatile profile and secretion of metabolites have been described after insect feeding and fungal infection, as has systemically-acquired resistance, herbivore-induced resistance and induced systemic resistance of plants, with the accumulation of jasmonate and salicylic acid and the activation of resistance genes [41,42]. These processes can be amplified when the host plant is a suboptimal food resource for the insect pest, as observed in our work, in which melon plants were clearly non-favorable for S. littoralis in terms of certain parameters of its life table, such as egg fertility [38,39]. In this context, Jaber and Vidal [25] suggested that the loss of volatiles or secretion of metabolites may be induced after mechanical damage to a plant (i.e., the collection of foliar discs).…”
Section: Discussionsupporting
confidence: 52%